2021
DOI: 10.1038/s41467-021-22535-z
|View full text |Cite
|
Sign up to set email alerts
|

TIM4 expression by dendritic cells mediates uptake of tumor-associated antigens and anti-tumor responses

Abstract: Acquisition of cell-associated tumor antigens by type 1 dendritic cells (cDC1) is essential to induce and sustain tumor specific CD8+ T cells via cross-presentation. Here we show that capture and engulfment of cell associated antigens by tissue resident lung cDC1 is inhibited during progression of mouse lung tumors. Mechanistically, loss of phagocytosis is linked to tumor-mediated downregulation of the phosphatidylserine receptor TIM4, that is highly expressed in normal lung resident cDC1. TIM4 receptor blocka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…As a possibility, the anti-tumor T cell responses might be activated by PC, through the antigen presentation in response to phagocytosis of immunogenic tumor vesicles or tumor fragments ( Dionisi et al, 2018 ; Li et al, 2018 ; Morris et al, 2018 ). They might also be activated in response to PC phagocytosis of whole tumor cells, which could facilitate the antigen presentation to CD4 + T cells as occurs with some professional antigen-presenting cells ( von Roemeling et al, 2020 ; Caronni et al, 2021 ). In addition, the increased protein expression of some genes associated with the phagosome function ( Supplementary Figure S2 ) also supports the immunogenic phenotype of CMA-deficient PC.…”
Section: Discussionmentioning
confidence: 99%
“…As a possibility, the anti-tumor T cell responses might be activated by PC, through the antigen presentation in response to phagocytosis of immunogenic tumor vesicles or tumor fragments ( Dionisi et al, 2018 ; Li et al, 2018 ; Morris et al, 2018 ). They might also be activated in response to PC phagocytosis of whole tumor cells, which could facilitate the antigen presentation to CD4 + T cells as occurs with some professional antigen-presenting cells ( von Roemeling et al, 2020 ; Caronni et al, 2021 ). In addition, the increased protein expression of some genes associated with the phagosome function ( Supplementary Figure S2 ) also supports the immunogenic phenotype of CMA-deficient PC.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our experience (and previously reported by Harusato et al. [1420]) cell yield is greatly reduced when this step is performed. [1416, 1421, 1422] The protocol described here for murine skin processing, can be used for analysis for total skin, or the epidermis and dermis separately. However, each method comes with its own drawbacks.…”
Section: Mononuclear Phagocyte Phenotypesmentioning
confidence: 99%
“…Using a protocol different from the one described here may result in higher expression levels of F4/80 on gut macrophages. Some publications report a heterogeneity of CD11c expression on gut macrophages [1425]. While we chose to focus on the CD11c + population, one may want to consider this when analyzing their data. Tim4 can be a useful marker to be added, for further delineation of macrophage populations [1416]; however, it also has been shown to be expressed on some DC populations [1422]. LCs are the main macrophage population in the epidermis.…”
Section: Mononuclear Phagocyte Phenotypesmentioning
confidence: 99%
“…Interestingly, a recent paper by Ruhland et al [35] showed a similar type of formation of cell-cell contacts and synapses between myeloid cells in tumor-draining LNs. Furthermore, a recent study using a murine lung tumor model demonstrated the crucial role of PtdSer receptor TIM-4 in DCs for uptake and cross-presentation of tumor-associated antigens to anti-tumor CD8+ T-cells [36].…”
Section: Discussionmentioning
confidence: 99%